Legal Formulation and the Direction of Legitimacy of the Carok Madura Tradition as Folklore for Strengthening National Identity - Evi Dwi Hastri; Rusfandi (Indonesian Scientific Publication, 2026)
This study examines the legal positioning of the carok tradition within the framework of Indonesian cultural and legal governance. Rather than approaching carok as a normative or value-laden practice, the research analyzes it as a socio-cultural phenomenon whose status remains legally ambiguous. Using a normative legal research method with a statutory and conceptual approach, the study explores how existing legal instruments regulate cultural preservation and how they relate to the transformation of traditional practices into recognized cultural expressions. The findings indicate that although various national legal instruments provide a general framework for cultural protection, they do not specifically regulate or classify carok as an object of cultural preservation. This regulatory gap limits its formal recognition within cultural policy and constrains its potential integration into cultural and creative development programs. The study concludes that a clearer legal framework is required to situate carok within the domain of cultural heritage, not as an endorsement of past practices, but as a regulated cultural expression aligned with principles of legal certainty, cultural preservation, and sustainable cultural development.